Epithelioid Hemangioma of the Spine: A Rare Case Report and Review of Literature - Vedagiri Vydia, Gautam; ., Ramaniah; ., Sadanand; ., Mukesh (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Epithelioid hemangioma (EH) of the spine is a rare vascular disease. Hemangiomas are tumors typically composed of thin-walled blood vessels, with EH representing an uncommon variant. While considered benign, EH can be locally aggressive. Although most commonly affecting the integumentary system, EH can also involve the liver, lungs, and bones. This case report presents a 25-year-old male with a comprehensive workup for EH, including clinical data, MRI spine, surgical findings, histopathological information, and adjuvant radiation therapy following surgical management. In addition to the case report, a review of the literature on EH of bones is provided. Case Presentation: A 25-year-old male presented to our emergency department with complaints of severe lower back pain and difficulty walking for the past three months. A previous MRI of the lumbosacral (LS) spine with whole spine screening, performed one month prior, revealed multifocal vertebral lesions involving the D4, D5, and D6 vertebrae, predominantly in the posterior elements. Expansion of the transverse processes, involvement of the costochondral junction, and the left 5th rib with extensive soft tissue component indenting on the pleura were also observed. The patient was evaluated by the neurosurgery team, and surgical decompression and stabilization of the D4-D6 vertebrae were planned. He underwent a D3-D6 laminectomy and stabilization under general anesthesia. Final histopathology, along with immunohistochemistry (IHC) correlation, confirmed a diagnosis of epithelioid hemangioma. The case was discussed at our hospital’s multidisciplinary tumor board, and adjuvant radiotherapy (RT) was recommended. The patient received a total dose (TD) of 45 Gray (Gy) to the D3-D6 region. Six months post-treatment, his power has improved and is near normal. Conclusion: This case exhibits typical features of EH, including a young male patient, lytic lesions with a sclerotic rim, and IHC confirmation.